2021
DOI: 10.3390/ani11092525
|View full text |Cite
|
Sign up to set email alerts
|

Insect Larvae Meal (Hermetia illucens) as a Sustainable Protein Source of Canine Food and Its Impacts on Nutrient Digestibility and Fecal Quality

Abstract: Insect larvae meal has been proposed as a sustainable protein source for animal diets. This study aimed to provide information on including black soldier fly larvae meal (BSFL; Hermetia illucens) in comparison to poultry meal (PM) in the canine diet with regard to digestibility and fecal characteristics. In light of this trend, the levels of PM or BSFL meal were added to replace about 30% of dry matter of the basic extruded diet. Six Beagle dogs (BW 9.64 kg) were included in a cross-over experiment. Dogs fed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The “food intake assessment” (palatability and speed of food intake) was divided into three scores in accordance with Abd El-Wahab et al [ 31 , 32 ]. Briefly, score 1 = lowest acceptance; score 2 = moderate acceptance; score 3 = maximum acceptance.…”
Section: Methodsmentioning
confidence: 99%
“…The “food intake assessment” (palatability and speed of food intake) was divided into three scores in accordance with Abd El-Wahab et al [ 31 , 32 ]. Briefly, score 1 = lowest acceptance; score 2 = moderate acceptance; score 3 = maximum acceptance.…”
Section: Methodsmentioning
confidence: 99%
“…For dogs fed commercial dry food based on lamb meal or BSFL, stool scores were not statistically different [ 99 ]. A study by Abd El-Wahab et al [ 100 ] compared the incorporation of BSFL meal compared to poultry meal (PM) in the diet of dogs in terms of digestibility and fecal characteristics. Following this trend, PM or BSFL meal was added to replace approximately 30% of the dry weight of the basic extruded diet.…”
Section: Digestibilitymentioning
confidence: 99%
“…The fecal dry matter content was higher in dogs fed the PM diet (33.0%) compared to those fed the BSFL diet (28.0%). These studies have shown that the inclusion of BSFL meal in dog food can be an appropriate source of protein without adversely affecting nutrient digestibility and stool quality [ 100 ]. In the studies by Penazzi et al [ 101 ], two diets containing venison meal (CTRL diet) or black soldier larvae (BSF diet) as the main sources of protein were analyzed.…”
Section: Digestibilitymentioning
confidence: 99%
“…Considerable attention has been paid to them as a unique, sustainable and natural source of protein for people and pets. (El-Wahab et al, 2021). A research by (Kilburn et al, 2020) established that inclusion of crickets in dog diet was acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…According to Yamka et al (2019), it has been demonstrated that dogs will consume diets that are dry with BSFL meal content of 5, 10, or 20%. According to El-Wahab et al (2021), adding BSFL meal to dog food can be a suitable source of protein with no adverse impacts on the digestibility of nutrients or quality of the faeces.…”
Section: Introductionmentioning
confidence: 99%